Heschl’s gyrus duplication pattern and clinical characteristics in borderline personality disorder: A preliminary study - Takahashi, Tsutomu; Sasabayashi, Daiki; Velakoulis, Dennis; Suzuki, Michio; McGorry, Patrick D.; Pantelis, Christos; Chanen, Andrew M. (Frontiers in Psychiatry, 2022)
Inter-individual variations in the sulco-gyral pattern of Heschl's gyrus (HG) might contribute to emotional processing. However, it remains largely unknown whether borderline personality disorder (BPD) patients exhibit an altered HG gyrification pattern, compared with healthy individuals, and whether such a brain morphological feature, if present, might contribute to their clinical characteristics. The present study used magnetic resonance imaging to investigate the distribution of HG gyrification patterns (single or duplicated) and their relationship to clinical characteristics in teenage BPD patients with minimal treatment exposure. No significant difference was noted for the prevalence of HG patterns between 20 BPD and 20 healthy participants. However, the BPD participants with left duplicated HG were characterized by higher prevalence of comorbid disruptive behavior disorders, with higher externalizing score compared with those with left single HG. Our preliminary results suggest that neurodevelopmental pathology associated with gyral formation might be implicated in the neurobiology of early BPD, especially for emotional and behavioral control.